Demographics Based Digital Literacy Level of National Hospital Employees as Digitizing Health Services Factor - Nevangga, Rizky Patria; Sasmita, Niken Sasadhara; Krsitiyono, Jokhanan; Prakosa, Adi Wasis (Jurnal Ilmu Komunikasi, 2023)
The government had imposed restrictions on community activities to overcome COVID-19. That impacted health services, mainly routine control queues for chronic disease patients. Digitalization of health services is a solution, but it needs to be supported by human resources with good digital literacy. This study aims to determine the relationship between the profile of hospital employees and health workers and the level of digital literacy at the National Hospital (NH). The theory used is about digital literacy and health services. Digital literacy is necessary for public health service units in the new media era. Increasing digital literacy among employees and paramedics in hospitals is a challenge. This research method uses descriptive quantitative, with a cross-sectional design. Demographic data and the level of digital literacy of NH employees were obtained using a questionnaire via Google Forms. Correlation analysis uses a significance test of the relationship between two variables; correlation and comparison are used as measurement analysis. The results show that the literacy level of NH employees is dimension two (2) with a proficiency level of 8 based on Digicomp 2.1. Productive age, women, undergraduate education, and the nursing profession has high digital literacy. This study concludes that the digitization of health services in NH is booming due to the high level of employee digital literacy with the employee profile above. This research contributes to an overview of employee profiles, which can be considered when recruiting employees.